Validated Risk Stratification System for Prediction of Adverse Events Following Open Reduction and Internal Fixation of the Ankle. Issue 3 (14th September 2018) - Bohl, Daniel; Holmes, George; Hamid, Kamran; Lin, Johnny; Lee, Simon
Category: Ankle Introduction/Purpose: As orthopaedic surgery moves towards bundled payments, there is growing interest in identifying patients at high risk for postoperative adverse events. The purpose of this study is to develop and validate a risk stratification system for the occurrence of adverse events following open reduction and internal fixation (ORIF) of the ankle. Methods: Patients undergoing ORIF of closed ankle fractures as part of the National Surgical Quality Improvement Program (NSQIP) were identified. For patients undergoing surgery during 2006-2014, multivariate Cox proportional hazards modeling was used to identify factors that were independently associated with the occurrence of adverse events (including events such as surgical site infection, myocardial infarction, and pulmonary embolism). Based on these results, a nomogram was used to generate a point-scoring system for risk stratification. To evaluate the validity of the point-scoring system, the system was applied to patients undergoing ankle ORIF during 2015-2016. Results: Of the 6, 140 patients undergoing surgery during 2006-2014, 5.8% developed an adverse event. Based on the Cox proportional hazards regression, patients were assigned points for each of the following statistically significant risk factors: anemia (+2 points), insulin-dependent diabetes (+2 points), age=65 (+1 point), dependent functional status (+1 point), chronic obstructive pulmonary disease (COPD; +1 point), and hypertension (+1 point; Figure 1A). 4, 702 patients were identified in the 2015-2016 validation cohort. Among these patients, the risk-stratification system was found to strongly predict the risk for adverse events (p<0.001, Figure 1B). Conclusion: The occurrence of adverse events following ankle ORIF is associated with anemia, insulin-dependent diabetes, age=65, dependent functional status, COPD, and hypertension. We present and validate a simple point-scoring risk stratification system to predict the risk of adverse events. Future systems of bundled payments for ankle ORIF should exclude high-risk patients from the bundling systems, or make appropriate adjustments in reimbursement based on risk.